Conditions for development dynamic strain steel ageing - Vakulenko, I. O.; Nadezhdin, Yu. L. (Science and Transport Progress, 2011)
Contrary to the one-sided straining, after compressive predeformation with subsequent tension the shift of appearing the first stress stall to higher values of strains can be observed. The values of compressive predeformation and the strain of first stress stall appearance are approximately equal.